Scalable Synthesis of 1,3,4,5-Tetraaryl Imidazolium Salts as Precursors of Sterically Demanding N-Heterocyclic Carbenes - Azap, Cengiz; Christoffers, Anna; Kadyrov, Renat (SynOpen, 2020)
A convenient, large-scale, and cost-efficient synthesis of 4,5-diarylsubstituted N,N-diarylimidazolium salts is described. A variety of 1,3,4,5-tetraaryl imidazolium salts with increasing electron donation and steric bulk of the N-aryl groups was synthesized in good yields. In the key step, readily available N,N′-diarylthioureas and benzoin/anisoin are coupled to give imidazole-2-thiones, followed by imidazolium salt formation by oxidative desulfurization. In this way, N,N-diarylimidazolium salts with 2-methoxy, 2-methyl, and 2-isopropyl substituents could be obtained; the synthesis of their 2-tert-butyl, 2,6-dimethyl, and 2,6-diisopropyl analogues failed.
Keywords: carbene ligands; heterocycles; imidazolium salts; imidazolinthiones; thioureas